Consumer-Brand Identification and Brand Loyalty: Analysis on Customer Satisfaction and Brand Trust as Mediators - Natalia, Dwike; Elgeka, Honey Wahyuni Sugiharto; Tjahjoanggoro, Anton Johannes (Psikostudia : Jurnal Psikologi, 2021)
Consumers who have used Apple-branded smartphones have greater probability that they will continue to buy iPhones in the future. This is because customers feel satisfied and have identified the product before making a purchase, creating loyalty for the Apple brand. The purpose of this study is to examine the role of customer satisfaction and brand trust as mediators in the relationship between consumer-brand identification and brand loyalty. Participants in this study consisted of 155 consumers and obtained by using accidental sampling technique. Data analysis used the Hayes Process model 4, which explains that customer satisfaction can act as a mediator in the relationship between consumer-brand identification and brand loyalty, while brand trust cannot act as a mediator. Brand loyalty is not sufficiently formed when consumers can identify the brand well or there is satisfaction with the brand, but rather by the essential emotional bond that makes consumers rely on the brand. However, this has not been fulfilled by the iPhone to make consumers have brand loyalty.